Persistence of Candida spp. in patients with inflammatory diseases of the respiratory and gastrointestinal tracts: analysis of laboratory studies in Kharkiv Region, Ukraine (2019–2021) - Bolshakova, H. M.; Minukhin, V. V.; Zhuravlova, I. V.; Golubka, O. V.; Chastii, T. V.; Kuchma, I. Y.; Savinova, T. V.; Shevchenko, Y. V. (Regulatory Mechanisms in Biosystems, 2025)
Invasive mycoses are becoming an increasingly serious threat in healthcare due to their continuous spread, the ability of pathogens to develop resistance to antifungal drugs, and the limited availability of new effective therapeutic agents for the treatment of fungal infections. Today, the most common causative agents of systemic mycoses remain fungi of the genus Candida , specifically C . albicans . Over the past decades, the epidemiological picture of candidiasis has gradually changed due to the increasing prevalence of C . glabrata and C . parapsilosis in mycotic pathology. The authors investigated the prevalence and species spectrum of Candida spp. as potential causative agents of candidiasis among subjects with inflammatory conditions of the respiratory and gastro intestinal tracts in Kharkiv region (Ukraine) during the period 2019–2021. The obtained results indicate a rising persistence of Candida spp. in the observed groups, increasing from 4.3% in 2019 and 4.7% in 2020 to 8.3% in 2021, with C . albicans identified as the predominant species, accounting for 82.8% of cases. Among the non- albicans group, C . krusei predominated (6.9%), while other Candida species were isolated significantly less frequently: C. glabrata , C. tropicalis , and C. kefyr were found in 4.3%, 3.4%, and 2.6% of cases, respectively. The susceptibility profile of isolated strains to itraconazole, fluconazole, and voriconazole was examined. Cand i da non- albicans strains exhibited increased resistance to itraconazole (42.8%) and voriconazole (57.2%), whereas C. albicans isolates demonstrated higher levels of fluconazole resistance (69.4%). The analysis of the obtained results suggests a further increase in infectious complications caused by fungi of the genus Candida among p a tients with inflammatory processes of the respiratory and gastrointestinal tracts, which may require mandatory laboratory control of mycotic infections and adjustments in therapeutic treatment to prevent invasive candidiasis.